STRATEGI PENGELOLAAN SDM BERBASIS TEKNOLOGI DIGITAL PADA SATUAN PENDIDIKAN ANAK USIA DINI KABUPATEN TANGERANG - Yossi Srianita (LPPM IAD Probolinggo, 2025)
This study aims to describe digital technology-based human resource (HR) management strategies in early childhood education (PAUD) units in Tangerang Regency. A descriptive qualitative approach was employed, with data collected through observation, interviews, and documentation involving unit heads, teachers, and educational staff. The results indicate that the use of digital technology in HR management remains limited to personnel administration, internal communication, and activity documentation. Meanwhile, the use of technology for recruitment, training, performance assessment, and the professional development of educators has not yet been optimally implemented. Necessary digital technology-based HR management strategies include enhancing the digital literacy of educators and staff, digitizing personnel administration, optimizing school communication platforms, and formulating internal policies that support technology-based HR governance. The findings suggest that implementing digital-based HR management has the potential to improve management efficiency, personnel data accuracy, communication effectiveness, and the quality of educational services in PAUD units.